Effects of Carbon Nanotubes on Asphalt Binder Rheology and Wearing Course Mixes - Shams, Mohammed K.; Hilal, Miami M.; Fattah, Mohammed Y.; Hafez, Mohamed (Civil Engineering Journal, 2025)
This study explores the influence of Carbon Nanotubes (CNTs) on the rheological and mechanical performance of asphalt binders and mixtures, with the objective of determining an optimal CNT content for enhanced pavement durability. CNTs were incorporated into asphalt binders at concentrations ranging from 0.5% to 2.0% by weight, and the modified binders were subjected to a comprehensive testing program. Rheological behavior was assessed using Rotational Viscosity (RV), Dynamic Shear Rheometer (DSR), Multiple Stress Creep Recovery (MSCR), and Bending Beam Rheometer (BBR) tests. Mechanical properties were evaluated through Marshall stability and Wheel Tracking tests, while microstructural characteristics were analyzed using Scanning Electron Microscopy (SEM) and X-ray Diffraction (XRD). The results demonstrated that CNT modification enhanced binder viscosity, high-temperature stiffness, and rutting resistance, with optimal performance observed at 1.5% CNT content. At this dosage, rutting depth was reduced from 15.0 mm to 6.2 mm, and Marshall stability increased from 11.7 kN to 17.4 kN. Additionally, tensile strength peaked at 1290 kPa, and moisture resistance (TSR > 86%) was significantly improved. However, higher CNT concentrations (>1.5%) resulted in particle agglomeration, adversely affecting workability and fatigue resistance. The findings identify 1.5% CNT as the optimal dosage, offering a balanced enhancement in performance without compromising binder flexibility.